Effect of Diet Energy Level on the Histological Characteristics of Testes of Indigenous Barred Cock in the Western Highlands of Cameroon - Ngoula, F.; Tadondjou , T.C.D.; Kana, J.R.; Kouam, M.; Mube, K.H.; Teguia, A. (International Journal of Poultry Science, 2019)
Background and Objective: This study was conducted to determine the effect of diet energy level on the histological traits of testes. Materials and Methods: For this purpose, ninety-six days-old barred male chicks, weighing 28.33 g in average were randomly divided into 12 groups of 8 chicks each. Three feeding programs (FP) each comprising a starter diet from day old to 12 weeks (S0: 2800 kcal kg–1, S1: 2900 kcal kg–1, S2: 3000 kcal kg–1) and a grower diet from 13-20 weeks (G0: 2900 kcal kg–1, G1: 3000 kcal kg–1, G2: 3100 kcal kg–1) were used and designated FP1, FP2 and FP3, respectively. Each of the FP was randomly distributed to 4 groups of 8 birds in a completely randomized design. At 20 and 30 weeks of age, 8 cocks from each treatment group were randomly slaughtered to determine the testes weight, the testicular shape index and the testes stereological and histological traits. Result: At 20 weeks of age, feeding programs FP0 and FP2 showed a significant increase (p<0.05) in the relative weight of testes, the seminiferous tubule area and diameter, the seminiferous tubule lumen area and diameter and the germinal cells thickness as compared to FP1. Focal foci were present in seminiferous epithelium of cock fed on FP0 and FP2, while they were absent in testes of cock treated with FP1. At 30 weeks of age, the seminiferous tubule lumen area was significantly higher (p<0.05) with FP0 as compared to values obtained with FP1 and FP2; meanwhile, germinal cells thickness was significantly higher (p<0.05) with FP1. The number and volume of foci were less important in testes of cocks fed on FP1 as compared to testes of cocks which received FP0 and FP2. Conclusion: In conclusion, the diet energy level of 2800 kcal kg–1 during the starter phase and of 2900 kcal kg–1 during the grower stage improved the testes histological and stereological traits of indigenous barred male chicken.